Perinatal outcome in preeclampsia at tertiary care center - Pawar, Anita G.; Yadav, Bhaurao B.; Chavan, Yogeshwari; Balvir, Shweta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: In India, preeclampsia and other hypertensive disorders of pregnancy are still one of the leading causes of adverse perinatal outcome. Methods: The observation descriptive study of preeclampsia with predetermined sample size of 195 was conducted at department of obstetrics and gynaecology at Government Medical College of Latur, over a time period of six month from March 2021 to August 2021. Findings are compared in frequency percentage values with the perinatal outcome of normotensive group from other study. Results: The prevalence of preeclampsia in our study was 4.1%. LBW found in preeclampsia group 32.3% versus 15% in normotensive group. Prematurity accounts for preeclampsia group 18.4% vs. 9% in normotensive group. Perinatal mortality rate is found to be 8.7 % vs. 2% in preeclampsia group vs. normotensive group respectively. Low APGAR score and NICU admission rate account for 14.8% vs. 13% and 16.4% vs. 11% respectively in preeclmpsia and normotensive group. Both FGR and oligohydroamnious accounts for 15.8% in preeclmpsia group. Important predictors of unfavourable perinatal outcome with p value significant (p<0.05), found in our study are severe and early onset of preeclampsia, severity of proteinuria and low birth weight. Conclusions: Adverse perinatal outcome in form of low birth weight, prematurity, fetal growth restriction and mortality is still high in preeclamsia patients than normotensive. So early diagnosis and treatment of preeclampsia is very crucial along with screening in high-risk patients to prevent unfavourable perinatal outcome.